Mos digital electronics - Cheng, Stephen Shao-Chung (World Scientific, 1987)
This book involves discreet signals and events, precisely dictated by appropriate logic funtions. Fundamentally all complex functions are built upon a few elementary simple logic. Solid state circuits perform logic as continuous physical changes, which represent and result in corresponding designated discreet stable logic levels.